Riverine spawning, long distance larval drift, and floodplain recruitment of a pelagophilic fish: A case study of golden perch (Macquaria ambigua) in the arid Darling River, Australia. Issue 4 (2nd March 2020) - Stuart, Ivor G.; Sharpe, Clayton P.
Abstract: Pelagic spawning riverine fish (pelagophils) spawn in free‐flowing river habitats with downstream drift of eggs and larvae but the spatial scale is often unknown, and this constitutes a major ecological knowledge gap. In the arid Darling River in south‐eastern Australia, the present objectives were: (i) to determine the potential downstream dispersal distance of young golden perch ( Macquaria ambigua ); and (ii) to evaluate whether provision of environmental water enhanced dispersal of young fish from Menindee Lakes to the lower Darling River (LDR) while also cueing further spawning in downstream lotic reaches. Golden perch spawned in unregulated lotic tributaries on a flood pulse and larvae drifted or dispersed >1, 600 km downstream and entered large ephemeral productive floodplain lake nursery habitats as fully scaled fingerlings. Planned releases of environmental water cued golden perch spawning in the LDR and enabled juvenile fish to disperse downstream from the Menindee Lakes nursery into receiving populations in the LDR, Great Darling Anabranch, and southern Murray River, with some fish potentially completing an active migration of >2, 100 km by age 1 year. The Darling River case study highlights the need for a system‐scale approach to the conservation management of pelagophilic fish, along with multi‐year perennial flow strategies to improve ecosystem integrity in large rivers globally.